Trend analysis of climate change and effect of climate-smart agricultural practices: the case of Humbo Woreda, Wolaita Zone, South Ethiopia - Tessema, Mefekir Woldegebriel; Atnafe, Addisu Damtew; Tora, Simon Emane; Bantider, Amare; Shure, Ergado (Frontiers in Climate, 2025)
This study investigates the trends of climate change and evaluates the effects of climate-smart agricultural (CSA) practices in Humbo Woreda, Wolaita Zone, Ethiopia. The findings revealed a significant increase in temperature and irregular rainfall patterns, which adversely affected agricultural productivity. This research employed a mixed-method approach, gathering data from household surveys, focus group discussions, and field observations. The key CSA practices adopted by smallholder farmers include agroforestry, soil and water conservation, and integrated soil fertility management. These practices were reported to enhance food security indicators, with 85% of the respondents noting improved income and 80% recognizing increased consumption after adopting CSA practices. Despite these positive outcomes, challenges such as low adoption rates and implementation barriers persist. This study underscores the need for targeted interventions to expand CSA adoption, improve farmers’ capacity, and address environmental vulnerabilities. Policymakers and stakeholders are encouraged to foster environments that support sustainable agricultural practices.